Helena Grabschrift-Taffet, a Krakow artist born in Tuchów - Natasza Styrna (Folia Historica Cracoviensia, 2021)
Helena Grabschrift was born on 18 April 1909 in Tuchów. Starting 1929, she studied at the Krakow Academy of Fine Arts, taught by such artists as Władysław Jarocki, Wojciech Weiss and Stanisław Kamocki. In late 1930s she became involved with the Krakow Association of Jewish Painters and Sculptors. She was one of the most active members of the organisation, and made arrangements for the last Krakow exhibitions of the works of Jewish painters before the war. For a long time, nothing was known of her life after the end of the Second World War; she was considered either dead or missing. The author of the present article managed to find sources confirming that the artist had survived the war, and to contact her family in Israel. Consequently, it was possible to add to the artist’s biography many new details from pre-war years, the period of Nazi occupation, as well as her later life in Israel, where she moved with her husband Henryk Taffet. Unfortunately, not much has survived from the artist's pre-war output, therefore the inter-war press remains the most important source of information about her work.